Deformational style in the foreland of the northern New Québec Orogen - Wares, Robert; Goutier, Jean (Geoscience Canada, 1990)
Summary The northern segment of the New Québec Orogen is divided into 4 zones, based on lit hostrat I graphic assemblages and deformational style. The tectonic fabric Is the result of WSW-SW transport during the third deformation event, which, in the foreland, consists of two stages. A basât décollement,low-angle thrust faults and bedding-parallel gliding in the western foreland are important features of the early D3 stage. The bulk of crustal shortening occurred during the late D3 (D3.) stage, which is characterized by large-scale, high-angle out-of-sequence thrusts, and folds. The hinterland records more complex pre-D3, deformation, which cannot presently be correlated with early deformation in the foreland. The D3. out-of-sequence geometry is probably the result of syntectonic erosion of the orogenic wedge, but there is little geological evidence in the foreland supporting this premise. This apparent paradox can be explained by Invokinga two-sided, double-wedge orogenic model, which links erosion and uplift In the hinterland to out-of-sequence thrusting in theforeland.